The Impact of Character Education on Student Discipline and Leadership - Sukmayadi, Dodi; Firayani (Kamara Journal, 2025)
This research aims to empirically examine the influence of character education on student discipline and leadership at the higher education level. The study identifies the causal relationship between the implementation of character education values instilled through academic and extracurricular activities and students' behavior in terms of discipline, as well as their ability to demonstrate effective leadership. The results suggest that character education, encompassing values such as responsibility, honesty, and cooperation, significantly impacts students' adherence to rules, punctuality, and leadership skills. By focusing on the development of both personal and social values, character education plays a crucial role in shaping students not only as academically capable individuals but also as morally responsible and effective leaders. Despite the widespread implementation of character education programs in higher education, the study highlights the need for more consistent and integrated application to ensure its effective impact on students' overall behavior. This research provides valuable insights for educational institutions to refine their character development strategies to better align with the demands of the contemporary world.